Astragaloside IV is a potential natural neuroprotective agent for stroke: a review - Zhang, Qiao-Li; Qin, Wen-Xiu; Li, Xiu-Juan; Zhang, Yun-Bo; Li, Ming; Xu, Jun-Feng; Mao, Zhong-Nan (Frontiers in Pharmacology, 2026)
Stroke poses a severe threat to human health, with limited therapeutic options currently available. Astragaloside IV (AS-IV), a primary bioactive metabolite derived from Astragalus membranaceus, exhibits multifaceted pharmacological effects, including anti-inflammatory, anti-fibrotic, and antioxidative properties. This review systematically examines recent advances in AS-IV research for stroke treatment, detailing its sources, physicochemical characteristics, mechanisms of action, and therapeutic efficacy in both in vitro and in vivo models. We critically analyze the potential of AS-IV as an adjunctive therapy for stroke, addressing current research hotspots, challenges, and emerging strategies. Notably, AS-IV synergistically enhances neuroprotection when combined with other plant-derived metabolites. This work provides a theoretical foundation for further development of AS-IV in stroke management. In summary, AS-IV demonstrates significant promise as a natural neuroprotective agent worthy of continued exploration for adjuvant stroke therapy.